Simplified formulation to evaluate forces due to shrinkage in composite steel-concrete beams with full shear connection - Rahal, Nacer; Beghdad, Houda; Souici, Abdelaziz; Zatir, Sara; Benmahdi, Khaled; Aouad, Halima (Vojnotehnički glasnik / Military Technical Courier, 2024)
Introduction/purpose: It has been known for a very long time that time-dependent effects such as creep and shrinkage of concrete considerably influence the behavior of composite steel-concrete beams. It is therefore very important to take these effects into account when calculating the strength and safety of composite steel-concrete beams. To this end, many theoretical and numerical research studies have been established to control this phenomenon. Most of this research presents laborious processes and calculations requiring complex techniques. Methods: This model consists of combining the static equilibrium equations and the two compatibility relations, in curvature and in deformation, of the composite steel-concrete cross-section with the differential equation resulting from the creep rate theory (RCM). The idea of this work was to take this model and simplify it to avoid difficult mathematical transformations. Results: The results from this simplified approach are very satisfactory when compared to those given by the analytical model. Conclusion: To overcome an excessive number of calculations and various difficulties associated with analytical or numerical methods to estimate additional stresses brought by the shrinkage of concrete in composite steel-concrete beams, a simplified analytical methodology has been proposed here while ensuring desired safety. This work has tried to simplify an existing analytical model based on the theory of linear viscoelasticity established in 2012.